The Influence of Peers on Student Learning Interests at SMKS Darel Hikmah Pekanbaru - Ayu Maharani; Hambali Hambali; Indra Primahardani (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The background of this research is regarding the influence of peers on students' learning interest. The influence of friendships and social activities of students with peers can be said to be quite strong, because in this phase the amount of time individuals spend with their peers is more than with their parents or family. The aim of this study was to find out whether there is peer influence on students' learning interest at Darel Hikmah Pekanbaru Vocational School. This type of research uses a descriptive quantitative approach, with data collection techniques using questionnaires, documentation and interviews. After considering the data and discussion, it was found that the F test yielded F_tab = 4.00 and F_hit = 15.470. Since F_hit is greater than F_tab, we can conclude that Ho is rejected and Ha is accepted. Based on this statement, the research hypothesis is accepted. In addition, the influence of Peers on Students' Interest in Learning is at a moderate level. Based on the results of the calculation above, it is explained that the value of the relationship (R) is 0.447. From the output, it is obtained a coefficient of determination (R Square) of 0.20 which implies that the independent variable (Peers) to the dependent variable (Student Learning Interest) is 20.0%. Based on the results and discussion in this study, it can be concluded that peers have a positive influence on student learning interest at Darel Hikmah Pekanbaru Vocational School.